the effects of aerobic training on physical performance in subjects with cardiac diseases - aberrahmane, sahraaoui; boussada, taha (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
التدريب البدني على أمراض القلب بعد حدث قلبي، ويعتبر النشاط البدني على هذا المستوى هو أحد المحددات الأساسية للصحة الجيدة. الهدف من عملنا هو معرفة تأثير إعادة تأهيل القلب على ممارسة الرياضة على الجانب البدني والسريري والنفسي في آثار التدريب الهوائية على الأداء البدني في المواضيع مع أمراض القلب، لتصبح على بينة من الإمكانات الفسيولوجية والنفسية للمرضى المستهدفين وكذلك توفير عناصر معلومات مفيدة عن مستوى التكيف الفسيولوجي للجسم من مرضى أمراض القلب والممارسة في إعادة تأهيل القلب. هذه الدراسة تم اجرائها في مؤسسة المستشفى التخصصي دكتور معوش مهند أمقران. وتم تغطية ملفات المرضى الذين جاءوا لأسباب تتعلق بأمراض القلب ويهدف متابعة برنامج إعادة تأهيل القلب. وشملت هذه الدراسة 65 مريضا من CNMS. فيما يتعلق بالفرضية الرئيسية، فإن الدراسة الحالية، بعد أن عالجت تطور بعض مرضى أمراض القلب قبل وبعد برنامج إعادة تأهيل القلب بالتمارين، سمحت لنا بوضع معايير مرجعية معينة لمراقبة وتقييم مستوى التكيف الفسيولوجي للجسم. إن إعادة التأهيل بالتمارين القلبية لها تأثير كبير على إعادة التأهيل البدني لدى مرضى القلب ولها تأثير نفسي إيجابي للغاية // // // // Heart disease remains the main cause of morbidity and mortality in the world, for this reason several studies have demonstrated the effectiveness of physical training on heart disease after a cardiac event, physical activity, at this level, is one of the essential determinants of good health. The objective of our work is to know the effect of cardiac rehabilitation to exercise on the physical, clinical and psychological aspect in the effects of aerobic training on physical performance in subjects with cardiac diseases, to become aware of the physiological and psychological potential of the targeted population as well as to provide elements useful information on the level of physiological adaptation of the body of cardiac diseases patients to exercise in cardiac rehabilitation. This is a retrospective and prospective study carried out in EHS - Specialized Hospital Establishment Dr Maouche Mohand Amokrane. centers and covering the files of patients who came for reasons of cardiac diseases and with the aim of following a cardiac rehabilitation program, this study concerned 65 patients from the CNMS. In relation to the main hypothesis, the present study, having treated the evolution of certain cardiac diseases patients before and after an exercise cardiac rehabilitation program and the parameters of two exercises tests, allowed us to put certain reference standards for the control and evaluation of the level of physiological adaptation of the body to the effect. Cardiac exercise rehabilitation has a significant impact on physical reconditioning in cardiac diseases patients and a very positive psychological impact.
LAPA-2024-25
Keywords: the effects of aerobic - physical performance - subjects with cardiac diseases // // أمراض القلب - التدريب البدني - الإمكانات الفسيولوجية والنفسية